Cara Belajar Siswa SMAN 1 Matur di Rumah pada Masa Pandemi Covid-19 - Rahmawati, Fitri; Santosa, Budi (Lembaga Yasin AlSys, 2023)
During the COVID-19 pandemic, students studied from home, affecting various aspects of student life, one of which was the way of learning. The aim of the research is to find out how students study at home during the COVID-19 pandemic. There were 5 student key informants, 1 Guidance and Counseling teacher and 3 parents. Data was collected through interviews, observation, and documentation. Data processing techniques use descriptive qualitative analysis and techniques to test the validity of the data with data trigulation. Based on the results of research on SMA N I Matur students, it shows that the way students learn during the COVID-19 pandemic is the first method of learning from the aspect of making a schedule, namely not carrying out all the schedules that have been arranged, and students not using their free time to the fullest. second, how to learn from the aspect of reading and taking notes, that is, there is still a lack of motivation for students to read, and in making notes students only make it in summary form. third, how to learn in the aspect of repeating lesson material, that is, students repeat lessons when they are going to face daily tests or exams. Fourth, how to learn from the aspect of concentration, that is, students can concentrate, but the student environment is less supportive. The five ways of learning from the aspect of doing assignments, namely, students rely on sources from the internet in doing assignments that are not sure of the truth of the source, and also if the internet network does not support the student's assignments will pile up.